Influencia de las pausas activas en el mejoramiento de la atención ejecutiva, durante la intervención áulica, en estudiantes de cuarto año de Educación General Básica de la Unidad Educativa Roberto Arregui, de la ciudad de Guaranda, provincia de Bolívar, año lectivo 2024-2025 - Cuascota Maldonado, Alexis Gonzalo (2025)
This study investigated the influence of active breaks in improving executive attention during the classroom intervention process with fourth-year students of basic general education at the Roberto Arregui educational unit in the city of Guaranda, province of Bolívar. The objective was to improve executive attention through the implementation of active breaks during the classroom intervention process, in order to improve their academic performance and promote more effective learning. A mixed methodology with a qualitative and quantitative approach was used, using surveys of students, interviews with teachers and parents. Through data analysis, the results revealed that incorporating active breaks helps improve concentration, reduce cognitive fatigue and increase class participation. It is concluded that active breaks are consolidated as an effective pedagogical strategy to optimize executive attention in the classroom. Therefore, a pedagogical intervention focused on providing practical guidelines to teachers for the implementation of active breaks in the school environment is proposed. To improve students' executive attention and academic performance.